APPLICATION OF INTELLIGENT SYSTEMS TO IMPROVE THE RELIABILITY AND EFFICIENCY OF POWER GRID OPERATIONS - STADNIK, MYKOLA; SHTUTS, ANDRII; KOLISNYK, MYKOLA; HRYHORENKO, NAZAR (Herald of Khmelnytskyi National University. Technical sciences, 2025)
Smart Systems are a crucial component of modern electrical power engineering, enabling improved reliability, efficiency, and stability in the operation of electrical networks. This article examines the implementation of smart technologies for monitoring, control, and optimization of energy systems. Particular attention is focused on the use of Artificial Intelligence (AI), the Internet of Things (IoT), and automated control systems to address challenges such as fault prediction, adaptive energy flow management, and the integration of renewable energy sources (RES).The article also explores mathematical modeling methods and MATLAB/Simulink software to assess the impact of smart systems on energy network performance. The results obtained demonstrate that the adoption of smart systems not only enhances the reliability of energy systems but also reduces maintenance costs and optimizes resource utilization.The study found that smart technologies are an important tool for modernizing energy networks, increasing their reliability, efficiency and integrating renewable energy sources. The use of modern technologies, such as the Internet of Things (AI) and automated control systems, allows not only to optimize energy flows, but also to significantly reduce energy losses and increase the stability of network operations. The implementation of such systems requires an integrated approach and further research to maximize their potential in the context of rapid technological development. In this context, the results of the study confirm the significant economic and technical effect of using smart energy network management systemsThus, the findings confirm that smart systems are a powerful tool for modernizing electrical power networks, promoting sustainable energy development, and ensuring the efficient use of energy resources for the integration of RES.The implementation of such systems requires a comprehensive approach and further research to maximize their potential in the context of rapid technological development. In this context, the results of the study confirm the significant economic and technical effect of using intelligent energy network management systems
Keywords: smart systems; electrical power engineering; renewable energy sources; research; optimization; automation